THE SUPPLY CHAIN REDESIGN OF CHILI COMMODITY IN LIRUNG DISTRICT TALAUD REGENCY - Banua, Rivan A.P; Massie, James D.D; Tasik, Hizkia H.D (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2017)
inside it, but the price is really high because of the poor supply chain system. This research conducted in Lirung District in Talaud Regency, with period of two months started from March ? May 2017. This research is qualitative research with descriptive study. The primary data is from interviewing the actors involve in supply chain system from upstream into downstream which is: farmer, collector, croupier, big retailer and retailer. the research find that, the supply chain needed to be redesign based on the situation and condition on the field by focusing on Time Efficient scenario, Cost efficient scenario, and Mix scenario, by removing big retailer and Croupier actors. The actors should maintain a good relationship and conducting continues transaction of the material flow with a professional payment system and proper communication, so there will be no bullwhip effect on the supply chain. The supply chain that recommended is based on Cost efficient and the government is needed to take a part in the supply chain as the croupier because government has the resources and ability to conduct that task. So there will be a transparency and flexibility in sharing information of market demand and price.Keywords: management, supply chain, logistic, supply chain management, chili commodity.